MIGRACJE ŻYDÓW POLSKICH ZE ZWIĄZKU RADZIECKIEGO NA DOLNY ŚLĄSK PO II WOJNIE ŚWIATOWEJ W RELACJACH ICH UCZESTNIKÓW - Banasiewicz-Ossowska, Ewa (Przegląd Wschodnioeuropejski, 2024)
The article presents migrations of Polish Jews from USSR to Lower Silesia in memories of their participants. The author uses the terms “repatriation” and “resettlement”, emphasizing their different meanings and the different situation of people returning from the USSR and leaving the former Polish lands. The source base is interviews conducted by the author among members of the Wrocław Jewish community and accounts of Lower Silesian Jews found in the Memory and Future Centre. The article focuses on the motivations of people applying for a trip to Poland; the conditions in which the journey took place and attempts to organize a new life. All adult respondents at that time voluntarily decided to repatriate or resettle and perceived it as the moment of ending the period of chaos and beginning a new stage. Some of the respondents experienced migration several times, and these experiences still evoked great emotions in them, affecting the quality of the narrative.